CHANGE OF LECTURERS’ ROLE IN APPLYING PROBLEM-BASED LEARNING IN UNIVERSITY STUDIES - Lenkauskaitė, Jurgita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article deals with the change in lecturers’ role that takes place when traditional study process is being replaced by problem-based learning. In problem-based learning a lecturer becomes a facilitator not authoritatively transferring knowledge to students but contributing to the construction of social knowledge, in which an important role is given to students’ knowledge conditioned by their unique experience, learners’ interaction, their relations with various subjects of social environment. Together with lecturer’s changing role problem-based learning also provokes the transformation of power relations in university studies. Facilitation that makes up the basis of a lecturer’s role in problem-based learning causes quite many challenges because it is an unstructured process requiring lecturer’s ability to flexibly respond to students’ learning needs, provide them adequate support in a right way and time, etc.